Transferring genes for arcelin protein from wild to cultivated beans: Implications for bruchid resistance - Harmsen, R.; Bliss, Fredrick A.; Cardona, C.; Posso G, Carmen Elisa; Osborn, Thomas C. (1987)
Four different types of arcelin, a protein that plays an important role in resistance to bruchids such as Zabrotes subfasciatus, were identified in wild accessions of Phaseolus vulgaris. Isogenic lines with cultivated black- (Porrillo 70) and white- (Sanilac) seeded parents were obtained by normal backcrossing of wild lines. The presence of arcelin hihgly affects the resistance parameters in lines derived both from Porrillo 70 and Sanilac. In lines derived from Sanilac, the life table of Zabrotes subfasciatus increased approx. 16 days, while in those from Porrillo 70, it increased 9 days. The strongest restriction effect was associated with the presence of arcelin-1, which decreased percentage of emergence up to 80 percent in both types of lines. Although the results are highly consistent in all Porrillo and Sanilac lines, the effect can vary given the difference observed in the levels of resistance to each arcelin type and because the lines differ in their degree of arcelin concn. in the seed, which is closely related with resistance to Zabrotes subfasciatus. (CIAT)